Resídue de polpas de frutas desidratadas na alimentação de leitões em fase de creche - Da Trindade Neto, Messias Alves; Petelincar, Izabel Marin; Berto, Dirlei Antonio [UNESP]; Moreira, José Aparecido; Vitti, Dorinha Miriam Silber S. (FapUNIFESP (SciELO), 2004)
It was evaluated chemically and biologically the powdered fruits pulp residue, used in human food industry. In the digestibility study it was used 12 commercial hybrids barrows piglets, with initial weight 12.2 ± 1,6 kg, allotted in individual cages. The treatments were a basal and a test diet. In the test diet the fruits pulp residue replaced 30% of the basal dry matter. The following values were obtained: dry matter 89,54%, starch 71,1%, glucose 5.4%, fructose 2,2%, crude protein 5,33%, gross energy 3771 kcal/kg, apparent digestible dry matter 96,01%, digestible energy 3448 kcal/kg, metabolizable energy 3389 kcal/kg. By bromatologic results and metabolism study, the powdered fruits pulp residue was characterized as an alternative to be evaluated in piglet diets. In the performance assay 90 piglets with initial weight of 6,60 ± 0,76 kg were allotted in a randomized block design, with six replications and three animals per experimental unit. The treatments were levels of powdered fruits pulp residue (0. 25, 50, 75 and 100%) replacing the corn of the control diet. The studied phases were initial-1 (14 days), initial-2 (21 days) and total period. On the performance there was no difference between the studied inclusion levels. For meal diets, the fruits pulp residue can replace the corn.
Powdered fruits pulp residue in the piglets feeding in the nursery phase
Keywords: Alternative food; Digestibilite; Metabolizabilite; Performance; Weaned; Animalia; Zea mays